Primitive and ancestor: ambivalence in the discourse of the indigenous notion in prehistory school textbooks, Colombia 1962-1974 - Cerón Rengifo, Carmen Patricia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper analyzes the written discourse that refers to people categorized as indigenous, in American and Colombian general prehistory school textbooks published between 1962 and 1974; a period that corresponds to the National Front. Elements of the social representations were examined through the resources proposed by the Critical Discourse Analysis. Close attention was paid to the way actors are named and differentiated via assignation of characteristics.  An ambivalent approach to the indigenous notion was identified, that is, the coexistence of negative and positive social representations. On the one hand, the indigenous are shown as previous and inferior to the European, through the primitive/civilized thinking scheme. On the other hand, it appears as an ancestor that gives antiquity to the nation and becomes part of the biological and psychological constitution of the people. These findings suggest this ambivalence represents a resource of elites' discourse to favor their position of power and, simultaneously, integrates the indigenous notion to the national and American identity, and the construction of alterity is maintained through racial hierarchy.